Priorities for survival - Lineberry, William P. (New York Wilson, 1973)
A compilation of articles concerned with man's prospects for survival in the ecological crisis, the virtues and vices of growth and technology, and the efforts made by governments and individuals to improve the environment.
Keywords: Environmental policy -- United States; Ecology; Environmental policy; Pollution